Material requirements planning method for controlling inventory of raw materials - Hendra Cipta; Rima Aprilia; Hari Kurniawan (Institute of Computer Science (IOCS), 2023)
The existence of shortages and excesses of production raw materials often occurs in the NR Brownies company where this situation greatly influences the smooth production process, especially in the supply of raw materials which results in sub-optimal expenditure costs. The aim of this research is to find solution how to prevent companies from experiencing these problems on a regular basis which results in less than optimal spending costs. In overcoming this problem, the Material Requirement Planning method is applied, this method is expected to minimize expenditure costs so that the benefits obtained are more optimal. From the research results, the Material Requirement Planning Method for EOQ calculations produces the minimum costs for sugar and oil raw materials of 18.295.130 and 19.591.230 respectively, while the POQ calculation produces the minimum costs for raw materials 14.839.500 for flour, 15.450.000 for eggs, 1.356.650 for cocoa flour, and 2.504.387 for baking powder.